Optic Neuritis and Childhood Herpes Zoster Ophthalmicus - Rajiv Garg; Siddharth Madan; Sarah Khan (Delhi Journal of Ophthalmology)
Optic neuritis is very rare sequelae of childhood Herpes zoster. Herpes zoster Ophthalmicus (HZO) is rarely seen in children. HZO optic neuritis resulting in no visual recovery in paediatric patients has been scantly reported. We report a six-year-old moderately malnourished male child suffering from HZO keratouveitis with optic neuritis who lost all vision in his right eye with a tumultuous course of two weeks of illness prior to his presentation to us. Prompt treatment with antiviral, high dose intravenous steroid and amniotic membrane grafting with a permanent tarsorraphy for a persistent non-healing neurotrophic corneal ulcer preserved globe integrity. Optic neuritis associated with childhood herpes zoster ophthalmicus is potentially blinding and refractory to medical management